(untitled) (Asia Pacific Journal of Social Innovation, 2024)
This study seeks to identify performance indicators suited to the Institution. Through MSU-lITe vision, mission, organisational strategies and outcomes, and existing Pla, including Pla mandated by CHED and DBM, as well as tho Balanced Scorecard (BSC) of various local end international academic institutions, and other literatures related to tho BSC, and with the participation of key respondents, this study came up with distinct Pls far the four BSC perspectives appropriate in the contest of MSU-IIT, using the Delphi Method integrated with Eisenhower’s Urgent/Important principle. Results show that an in-depth study of artant literatures provide a good position an how to go about each perspective of the BSC along with its Pls, Moreover, the Delphi Mothod is proven effective in drawing a consensus of what should and should not be put in the BSC. Further, incorporating Eisenhower’s Urgentlmportant principle made the selected P/s more substantial, accoptable and appropriate. Future studies may focus upon the improvement of the method of the study and implementation of the Balanced Scorecard of MSU-IIT.